KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF SOSIOLOGIS - Manan, Mohammad ‘Azzam (Jurnal Legislasi Indonesia, 2008)
In sociological perspective, this article shows that domestic violence is akind of criminal actions which is spread anywhere without ethnic groups,believes, and social status limitations. Although in the beginning domesticviolence is a privacy matter, it has been considered public interest and acriminal action due to the impact of any types of this violence to victimsphysically, sexually, and mentally are very bad and serious. As a criminalaction, domestic violence has been subjected to criminal punishment accordingto the Indonesian Law Number 23 the Year 2004 on the Elimination of DomesticViolence. In addition, it is also considered violence toward humanity based onthe human rights principles. However, in the present day there are strongindications that domestic violence in Indonesia from time to time increases innumber.The objective of this discussion is to get an explanation on direct andindirect factors leading to this social problem. In addition, the purpose of thestudy is also aimed to recommend how to eliminate or at least to decreasedomestic violence as a social problem in number. This study found that thosefactors are able to be divided into two categories, i.e. internal and externalfactors. The internal factors mean any kinds of actors’ and victims’characteristics connecting with their social background and status. In theother hand, the external factors are all cultural value systems, incompatibleconditions, especially conflict and anomie situation, and economy problems.Over all, domestic violence occurs due to the abuse of power.In order to eliminate domestic violence in every level of actions, all factorsleading to the problem in society should be removed by strengthening socialnetworking, understanding local wisdom, and strengthening economicfoundation and structure. Moreover, the implementation of religion messagesin a daily real life should also be conducted by every actors of any household.